Endovascular Thrombectomy for Stroke Effectiveness Study—An Audit From a Small Tertiary Care Center. Issue 1 (February 2020) - Virani, Karim; Hu, Sherry; Christian, Christine; Simpkin, Wendy; Phillips, Stephen; Shankar, Jai Jai Shiva
Purpose: Endovascular thrombectomy (EVT) treatment for acute ischemic stroke is now recommended as a standard of care. However, implementing EVT in routine clinical practice poses many challenges, even in countries with advanced health-care systems. The aim of the current study is to delineate if EVT at our institution is an effective treatment for acute ischemic stroke. Methods: All patients who underwent EVT at our institution between December 2011 and July 2017 were retrospectively assessed from our prospective registry. Clinical and imaging (including the Alberta Stroke Program Early CT [ASPECT] score, single-phase computed tomography angiography, and computed tomography perfusion) criteria were utilized to determine EVT suitability. Primary outcomes included modified Rankin score (mRS) at 90 days and recanalization determined by the modified Treatment in Cerebral Infarction score. Effectiveness was assessed by comparing our cohort with patients receiving EVT in the ESCAPE (Endovascular Treatment for Small Core and Proximal Occlusion Ischemic Stroke) trial. Results: Eighty-eight patients presented to our hospital after a median of 87 minutes last seen normal. Of these, median ASPECT score was 9. A majority (72%) also received intravenous alteplase. Successful recanalization (≥TICI 2b) was achieved in 79%. At 90 days, 48% (36/75) were functionally independent (mRS score of 0-2) and 28% (21/75) were disabled (mRS score of 3-5); 24% (18/75) died (mRS of 6) within 90 days. Conclusions: An audit of our initial experience with EVT for the treatment of acute ischemic stroke in a small tertiary care center yielded similar results compared to the ESCAPE trial, which is encouraging for implementing this treatment in routine clinical practice.